Mean platelet volume as a risk factor in pregnant diabetic women - Sayed M. Abel-Rahman; Essam S. Badawy; Ahmad A. Amer; Dalal Fekry (SpringerOpen, 2012)
Background Diabetes is an established risk factor for cardiovascular disease (CVD); therefore, the subset of women with gestational diabetes mellitus (GDM) who develop type 2 diabetes mellitus is at an increased risk for developing CVD in the future. Objectives To assess the platelet count and mean platelet volume (MPV) of pregnant women with GDM and gestational impaired glucose tolerance (GIGT) to determine whether GDM and GIGT are risk factors for future development of CVD. Patients and methods A 50 g oral glucose load (OGL) was administered to all participants (400 pregnant women), and routine hematologic parameters and MPV were studied at 24-28 gestational weeks using a Beckman/Coulter MAXM Hematology Analyzer. When a plasma glucose level of at least 140 mg/dl was measured after administering OGL, a 100 g 3-h oral glucose tolerance test was performed. Of these women, 296 (74%) had normal oral glucose tolerance, 48 (12%) had GIGT, and 65 (14%) had GDM. The mean platelet counts were higher in the normal OGL group than in the GIGT group, and higher in the GIGT group than in the GDM group, with no statistically significant differences among the three groups. However, MPV was significantly higher in the GDM group than in the normal glucose level group (P<0.05). Also, women with high MPV values had lower platelet counts. Results A significant difference was observed for MPV values between the GDM and normal OGL groups. Conclusion Presence of a high MPV in cases of GDM could indicate an increased risk for current and future thrombotic complications.